Regulating Girls and Women: Sexuality, Family, and the Law in Ontario, 1920-1960 - Srigley, Katrina (Labour / Le Travail, 2003)
The article reviews the book "Regulating Girls and Women: Sexuality, Family, and the Law in Ontario, 1920-1960," by Joan Sangster.
Keywords: BOOKS – Reviews; Nonfiction; REGULATING Girls & Women: Sexuality; Family & the Law in Ontario 1920-1960 (Book); SANGSTER; Joan; WOMEN – Legal status; laws; etc.